2006
DOI: 10.1177/0261018306062596
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the politics of service provision for adults with a history of childhood sexual abuse

Abstract: This paper reviews the evidence on the relevance of gender to the prevalence and impacts of sexual abuse in childhood, and to the interaction between adults with a history of child sexual abuse ('survivors') and services. It is widely acknowledged now that child sexual abuse increases the risk of a range of problems in adult life, that a wide range of services can offer reparative experiences, and that there is also a risk of retraumatization if the dynamics of abuse are replicated. Points where gender may aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…These findings are consistent with research that has called for more services and culturally competent clinical treatment (Liu, 2005). Many clinical services for abuse survivors are designed to meet the needs of women (Hooper & Warwick, 2006). However, in recent years, there has been an increase in the availability of male-specific resources ranging from self-help books (e.g., Lew, 2004) and online resources (e.g., 1in6.org) and national survivor organizations have emerged, such as MaleSurvivor, a membership organization that holds conferences and offers support services for men recovering from sexual victimization; however survivors may not be aware of these organizations.…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with research that has called for more services and culturally competent clinical treatment (Liu, 2005). Many clinical services for abuse survivors are designed to meet the needs of women (Hooper & Warwick, 2006). However, in recent years, there has been an increase in the availability of male-specific resources ranging from self-help books (e.g., Lew, 2004) and online resources (e.g., 1in6.org) and national survivor organizations have emerged, such as MaleSurvivor, a membership organization that holds conferences and offers support services for men recovering from sexual victimization; however survivors may not be aware of these organizations.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with Fillingim et al. [2] and Hooper and Warwick [55], it is plausible that among men, unresolved emotions related to abuse may have found a more socially accepted or less stigmatizing route to be expressed, potentially through increased pain perception or emotional response to pain. This also supports Spertus et al.…”
Section: Discussionmentioning
confidence: 56%
“…Nonetheless, the sexual abuse rate for men in our sample is higher than in most other studies. Hooper and Warwick [55] found that males are often in contact with their providers for many years before disclosing a sexual or physical abuse history, where women are more likely to disclose an abuse event early on in their patient-physician interactions. This may reveal a reluctance on the part of men to share this information before trust is well established.…”
Section: Prevalence and Consequences Of Abusementioning
confidence: 99%
“…Women also discussed their search for interventions that could recognize their need for support that would not compromise their reweaving work. Women explained that prescriptive rules, routines, and expectations accompanied by blame and censure seriously challenged their reweaving efforts because these led to a sense of powerlessness reminiscent of childhood experiences (Hooper & Warwick, 2006) and to feelings of marginalization (Vasas, 2005) and stigmatization (Courtwright, 2009).…”
Section: Implications For Future Researchmentioning
confidence: 99%